Mesoscopic Stacking Reconfigurations in Stacked van der Waals Film - Heo, Yoon Seong; Kim, Tae Wan; Lee, Wooseok; Choi, Jungseok; Park, Soyeon; Yeom, Dong Il; Lee, Jae Ung (Small, 2024)
Mesoscopic-scale stacking reconfigurations are investigated when van der Waals (vdW) films are stacked. A method to visualize complicated stacking structures and mechanical distortions simultaneously in stacked atom-thick films using Raman spectroscopy is developed. In the rigid limit, it is found that the distortions originate from the transfer process, which can be understood through thin film mechanics with a large elastic property mismatch. In contrast, with atomic corrugations, the in-plane strain fields are more closely correlated with the stacking configuration, highlighting the impact of atomic reconstructions on the mesoscopic scale. It is discovered that the grain boundaries do not have a significant effect while the cracks are causing inhomogeneous strain in stacked polycrystalline films. This result contributes to understanding the local variation of emerging properties from moiré structures and advancing the reliability of stacked vdW material fabrication.
Keywords: Atomic reconstruction; Mechanical; Mesoscopic scale; Mesoscopics; Moire superlattice; Stacking structures; Stackings; Thin-films; Transfer process; Van der Waals films; atomic reconstructions; moiré superlattice; Raman spectroscopy; van der Waals film